2015
DOI: 10.2118/169088-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Field-Representative Enhanced-Oil-Recovery Coreflood Method

Abstract: This study describes a new method that can improve laboratory determination of enhanced-oil-recovery (EOR) potential for a test fluid relative to a base fluid. The new method uses a modified steady-state fractional-flow method to measure the shift in oil saturation in a rock at an intermediate fractional flow when changing from a base brine to a test EOR brine(s). This study uses fractional-flow analysis and simulations to illustrate the new method and compare it with the conventional-unsteady-state approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Herein it has been shown that instead of using just SO 4 2ions using PO 4 3and /or BO 3 3can also increase the oil production (Gupta et al 2012;Vo et al 2012). The study also shows that neither SO 4 2nor Ca 2ϩ /Mg 2ϩ is necessary for obtaining an increased in oil production the study also recommends that neither mineral dissolution/precipitation nor soluble ion based wettability alteration can explain various EOR experiments (Gupta et al 2015).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Herein it has been shown that instead of using just SO 4 2ions using PO 4 3and /or BO 3 3can also increase the oil production (Gupta et al 2012;Vo et al 2012). The study also shows that neither SO 4 2nor Ca 2ϩ /Mg 2ϩ is necessary for obtaining an increased in oil production the study also recommends that neither mineral dissolution/precipitation nor soluble ion based wettability alteration can explain various EOR experiments (Gupta et al 2015).…”
Section: Introductionmentioning
confidence: 86%
“…Particularly during tertiary (enhanced) oil recovery the effluent brine can play a dominant role particularly when the salinity and composition of the injection brine is varied significantly (Zhang et al 2006;Zhang et al 2007;Zahid et al 2010;Austad et al 2005;Puntervold et al 2009;Gupta et al 2012;Strand et al 2008;Strand et al 2006). There are three general enhanced oil recovery methods involving variation in composition and salinity of injected brine which includes low salinity brine injection (Zahid et al 2011;Austad et al 2011;Romanuka et al 2012;Pu et al 2010) smart water enhanced oil recovery (Austad et al 2005;Zhang et al 2006;Zahid et al 2010) and advanced ion management (Gupta et al 2012;Gupta et al 2015;Vo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was first shown that either altering the brine composition or reducing the salinity of injected brine below that of the initial formation water can lead to additional oil recovery for Berea sandstone [6][7][8][9][10][11][12]. Such results attracted many oil and gas companies, such as British Petroleum [13][14][15][16][17][18][19], Shell [20][21][22][23][24][25][26], ExxonMobil [27,28], Schlumberger [29][30][31], TOTAL [32,33], and Statoil [34,35] to investigate and further explore the potential and applicability of low salinity waterflooding (LSW) for improved oil recovery. LSW, also known as designer waterflood, advanced ion management, and smart waterflooding, injects brine with controlled ionic concentration and composition (also known as smart water or dynamic water) into the well [17,20,27].…”
Section: Introductionmentioning
confidence: 99%